2015
DOI: 10.1093/mnras/stv784
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological constraints from weak lensing peak statistics with Canada-France-Hawaii Telescope Stripe 82 Survey

Abstract: We derived constraints on cosmological parameters using weak lensing peak statistics measured on the ∼ 130 deg 2 of the Canada-France-Hawaii Telescope Stripe 82 Survey (CS82). This analysis demonstrates the feasibility of using peak statistics in cosmological studies. For our measurements, we considered peaks with signal-to-noise ratio in the range of ν = [3, 6]. For a flat ΛCDM model with only (Ω m , σ 8 ) as free parameters, we constrained the parameters of the following relation Σ 8 = σ 8 (Ω m /0.27) α to b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 79 publications
4
63
0
Order By: Relevance
“…2 Canada-France-Hawaii Telescope Lensing Survey (CFHTLenS) [10], the 130 deg 2 CFHT-Stripe 82 survey [11], and the 139 deg 2 Dark Energy Survey (DES) Science Verification run [12]. All results are consistent with constraints from second-order statistics.…”
Section: Degmentioning
confidence: 56%
“…2 Canada-France-Hawaii Telescope Lensing Survey (CFHTLenS) [10], the 130 deg 2 CFHT-Stripe 82 survey [11], and the 139 deg 2 Dark Energy Survey (DES) Science Verification run [12]. All results are consistent with constraints from second-order statistics.…”
Section: Degmentioning
confidence: 56%
“…The same is true for other large-scale structure probes not shown in Fig. 4 such as the CFHTlens weak lensing shear survey (Heymans et al 2013), the peak statistics of lensing (Liu et al 2015;Kacprzak et al 2016), or the Sunyaev-Zeldovich cluster counts (Ade et al 2016). The contours from Planck15 (Ade et al 2015), on the other hand, do not agree with the observed velocity function at the 2-σ level.…”
Section: Cosmological Parameter Estimationmentioning
confidence: 69%
“…Such weak lensing mass maps provide an important means of studying the large-scale structure of the Universe as well as non-Gaussian features of the matter density field. For example, massive clusters of galaxies can be identified from peaks in mass maps (e.g., Miyazaki et al 2002Miyazaki et al , 2007Wittman et al 2006;Shan et al 2012;Utsumi et al 2014;Liu et al 2015). Correlations of mass maps with light maps constructed from galaxies and clusters of galaxies can reveal the connection between mass and light, by constraining mass-tolight ratios and galaxy biases (e.g., Hoekstra et al 2002;Okabe et al 2010;Jullo et al 2012;Chang et al 2016;Pujol et al 2016;Utsumi et al 2016).…”
Section: Introductionmentioning
confidence: 99%